2010
DOI: 10.3851/imp1696
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B surface antigen concentration correlates with HBV DNA level in patients with chronic hepatitis B

Abstract: Serum HBsAg concentration might serve as a surrogate marker of HBV DNA level in CHB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 27 publications
5
71
1
1
Order By: Relevance
“…Previous studies had demonstrated that serum HBsAg level could be used as a predictive marker of serum HBV DNA for patients infected with HBV (Su et al, 2010;Sun et al, 2012). As expected, our data show that serum HBV DNA, HBeAg, and HBsAg level could discriminate seminal HBV DNA-positive patients from seminal HBV DNA-negative patients.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies had demonstrated that serum HBsAg level could be used as a predictive marker of serum HBV DNA for patients infected with HBV (Su et al, 2010;Sun et al, 2012). As expected, our data show that serum HBV DNA, HBeAg, and HBsAg level could discriminate seminal HBV DNA-positive patients from seminal HBV DNA-negative patients.…”
Section: Discussionsupporting
confidence: 87%
“…More on-treatment decline of qHBsAg has been shown in patients with IFN-based therapy than in those with NUC therapy (Su et al 2010). Recent data further revealed the correlation between the declines of qHBsAg and HBV genotype in patients receiving IFN-based therapy .…”
Section: Interferon-based Therapymentioning
confidence: 99%
“…HBsAg levels were quantified using the Architect HBsAg QT assay (Abbott Laboratories, Abbott Park, IL) according to the manufacturer's instructions. 12,19,20 The detection range of the Architect assay is 0.05-250 IU/mL; if the HBsAg level was found to be higher than 250 IU/mL, the samples were diluted to 1:100 to 1:1,000 to obtain a reading within the calibration curve range.…”
Section: Methodsmentioning
confidence: 99%